Preventing Pulmonary Tuberculosis In Children By Empowering The Kids Cadres - Yulia Khairina Ashar; Wahyudi Wahyudi; Putra Apriadi Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Pulmonary tuberculosis (TB) is an infectious disease caused by tuberculosis germs (Mycobacterium tuberculosis). This disease is still a global health problem. It is estimated that one third of the world's population has been infected with pulmonary TB, where the majority of pulmonary TB sufferers are of productive age (15-50 years). Pulmonary TB is chronic and is typically characterized by the formation of granulomas and tissue necrosis. Pulmonary TB can be transmitted through the air, when someone with active TB in the lungs coughs, sneezes or talks. The research method used in this research is quasi experimental research with a one group pretest-posttest research design. The location of the research was in Aceh Singkil Regency. The research was carried out from July to December 2023. The research sample was 30 representatives of junior high school students based on school recommendations. The research results showed that 23 (38.3%) respondents had knowledge about eating nutritious food, and 25 (83.3%) respondents had the attitude that if they were suffering from TB, they would go to the health center. The conclusion is that students' knowledge and attitudes have increased by being given TB training, especially knowledge about TB being caused by heredity and consuming nutritious food.